Prawo negacji negacji w dziejach refleksji nad językiem naturalnym - Zabrocki, Władysław (Investigationes Linguisticae, 2007)
The paper deals with the philosophical assumptions of linguistic theories. It is concerned with three paradigms of linguistic thought (generativist, structuralist, and historical-comparative). Its main thesis is a proposal to treat the psychological approach assumed by generativists as a peculiar dialectical transformation of the psychological assumptions of the historical-comparative linguistics.